Extensive disseminated cysticercosis: a case report in Yunnan province, China - Xin-Zhong Zang; Huan-Zhang Li; Men-Bao Qian; Ying-Dan Chen; Chang-Hai Zhou; Hong-Kun Liu; Yu-Hua Liu; Shi-Zhu Li (BMC Infectious Diseases, 2019)
Abstract Background Cysticercosis is spreading all over the world and it is a major health problem in most countries of Latin America, Africa, and Asia. Extensive disseminated cysticercosis is relatively rare and fewer than 120 case have been reported in the worldwide. We reported a rare case of extensive disseminated cysticercosis in Yunan province, China. Case presentation A rare case of extensive disseminated cysticercosis, in a 61-year-old male Chinese was detected from Yunnan province in 2018. Clinical and etiological examination was performed, as well as the epidemiological investigation. Conclusion The life cycle of T. solium in the area where the case came from is complete. We expect this case could raise the attentions to the control of Taenia solium infection and subsequent cysticercosis there.